Factors Influencing the Completeness of Basic Immunization for Infants in the Catchment Area of Simpangkatis Health Center, Central Bangka District, 2023 - Monica; Harmendo; Asmaruddin, M. Fahd; Hemingway, Ernest (Universitas Nahdlatul Ulama Surabaya, 2024)
Immunization plays a crucial role in children’s development by preventing various dangerous diseases and disabilities such as chickenpox, polio, and tuberculosis. This research employed an analytical method with a cross-sectional study design. Data was collected through questionnaires in September 2023, with a sample size of 91 respondents. The study’s findings revealed significant relationships between the level of maternal education (p = 0.025), maternal knowledge (p = 0.024), and maternal employment status (p = 0.021) with the completeness of basic immunizations for babies. However, family support did not show a significant relationship (p = 0.074) with immunization completeness. In conclusion, maternal education, knowledge, and employment status significantly influence the completeness of basic immunizations for infants. However, family support does not appear to play a significant role in ensuring immunization completeness in the work area of the Simpangkatis Health Center, Central Bangka Regency, in 2023.